Effect of Straw and Wood Ash on Soil Carbon Sequestration and Bacterial Community in a Calcareous Soil - Zhao, Huili; Ahmad, Shakeel; Wu, Nan; Suo, Lizhu; Tian, Xiaohong; Zhao, Ying; Yu, Jinyi; Wang, Li; Si, Bingcheng (Frontiers in Microbiology, 2022)
The effective utilization of agricultural waste can improve soil fertility. Straw provides energy for the soil, and wood ash supplies nutrients to enrich the soil. However, few studies have examined the effects of wood ash and straw on the sequestration of soil carbon and the soil bacterial community, particularly in calcareous soils. The goal for this study was to quantify the impact of a combination of wood ash and straw on the indicators described above using stable δ13C isotope analyses by applying wheat straw (a C3 plant) to a calcareous soil under a long-term C4 crop rotation. The incubation experiment included four treatments as follows: (i) no amendment (Control); (ii) amendment with wood ash (W); (iii) amendment with straw (S); and (iv) a combined amendment of straw and wood ash (SW). The results showed that sequestration of soil inorganic carbon (SIC) in the SW and W treatments was obviously higher than that in S and Control treatments. The sequestered soil organic carbon (SOC) in the SW treatment was 1.25-fold greater than that in the S treatment, while there was no evident effect on the SOC content compared with straw alone. The microbial biomass carbon and dissolved organic carbon derived from microbial biomass in the four treatments was distributed as SW > S > W > Control. The pH and electrical conductivity were obviously higher in the W and SW treatments than in the S treatment and the Control. The SW was conducive to the maintenance of soil enzymatic activities and bacterial diversity. Bacteroidetes and Actinobacteriota dominated in SW, while the Acidobacteria phyla dominated in S treatment. The diversity of bacteria in the soil and community composition of the bacteria was predominantly assessed by the levels of soil labile carbon, pH, and electrical conductivity. The incorporation of straw and wood ash is probably more effective at improving SIC and SOC sequestration and ameliorates the soil microhabitat.